Spiritual Science: Why Science Needs Spirituality to Make Sense of the World by Steve Taylor - Grosso, Michael (Journal of Scientific Exploration, 2019)
Ever since the rise of modern science in 17th century Europe, science and spirituality have been estranged. This has been worse than unfortunate because science and spirituality are major parts of human experience, and it won’t do to have them perennially at odds with each other. So one of the mega thought-memes of modern history has been trying to harmonize these two dimensions of experience that so powerfully influence our lives. The challenge is how to integrate them and do justice to the best they have to offer while being wary of the worst as well. Much of modern thought has struggled to make the divided soul of Western humanity whole and to reintegrate a broken human identity. The task becomes more urgent today when the fractures and conflicts of human society are growing, alongside looming climate catastrophe, with secular scientists and public intellectuals like Noam Chomsky and Helen Caldicott talking about doomsday and apocalypse.[i] Fortunately, there are those anxious to make the case for the marriage of science and spirituality. Dr. Steve Taylor, a senior lecturer in psychology at Leeds Beckett University, UK, offers readers an informed guidebook to that possible marriage, Spiritual Science: Why Science Needs Spirituality to Make Sense of the World. The title is clear and to the point, as is the writing throughout. Taylor is fully aware of the unorthodox nature of his views, given that the word spiritual is a pariah in today’s mainstream intellectual world. Worse, to use spiritual to modify science is clearly heretical. But Taylor is not apologetic: “. . . our culture is in thrall to a particular paradigm or belief system that in its own way is just as dogmatic and irrational as a religious paradigm” (p.2). We should resist being forced into a “false dichotomy” between dogmatic religion and reductive materialism when in fact both stances need to yield to a new paradigm that transcends their limitations. [i] Caldicott, H. Ed.(2017) Sleepwalking to Armageddon: The Threat of Nuclear Annihilation. New York: The New Press.